IT-PRONOMINAL REFERENCE COHESION DEVICE AND THE TRANSLATION INTO INDONESIAN IN DESCRIPTIVE TEXT ENTITLED “THE CULTURAL AND POLITICAL DRAIN” - Km Tri Sutrisna Agustia (LPPM Universitas Dhyana Pura, 2016)
ABSTRACT Translation is a process of change the form of a text from one language to another languagewithout losing the meaning of the text itself. In the process, the translation requires an adequate understanding of detail that greatly affect the outcome of the translation itself. In this paperdiscussed about how the translation process pronoun it sourced from deksriptip text with Englishas the source language and Bahasa Indonesia as the target language. In addition to the translation process, one other thing that can be studied in this paper is on the level of accuracy in thetranslation of the pronoun it. Found that in the translation process found some low degree of translation accuracy. It was caused by a translator can not find the equivalent terms andgrammatical structure of the text. Keywords: translation, meaning, pronoun, equivalent, grammatical structure ABSTRAK Penerjemahan merupakan proses perubahan bentuk sebuah teks dari bahasa satu ke bahasayang lain tanpa kehilangan makna dari teks itu sendiri. Dalam prosesnya, penerjemahan memerlukan pemahaman detail yang memadai yang sangat mempengaruhi hasil dari terjemahanitu sendiri. Dalam tulisan ini dibahas mengenai bagaimana proses penerjemahan pronomina it yang bersumber dari teks deksriptip dengan Bahasa Inggris sebagai bahasa sumber dan BahasaIndonesia sebagai bahasa target. Selain proses penerjemahan, satu hal lain yang ditelaah dalam tulisan ini adalah mengenai tingkat akurasi dalam penerjemahan pronomina it itu sendiri. Ditemukan, bahwa dalam proses penerjamahan ditemukan beberapa tingkat akurasi penerjemahan yang rendah. Hal itu disebabkan oleh penerjemah yang tidak dapat menemukanistilah dan susunan gramatikal teks yang sepadan dari bahasa sumber ke bahasa target. Kata kunci: penerjemahan, makna, pronomina, sepadan, susunan gramatikal